2013
DOI: 10.5539/jas.v5n11p75
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Genotype x Environment Interaction for Grain Yield in Maize Hybrids

Abstract: Maize is an important staple crop for millions of people in Sub-Saharan Africa. The crop grows in a wide range of environmental conditions. The present study was performed to analyze the genotype-by-environment (G×E) interaction for grain yield of fourty two single cross hybrids grown in three environments located at different agro-ecological zones of Kenya. The maize genotypes were grown in randomized complete block design with three replicates in 2006 and 2007. Grain yield data of the single cross hybrids wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
24
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 14 publications
9
24
0
9
Order By: Relevance
“…conditions were also reported by Agrwal et al., (2000), Dodiya and Joshi (2003), Nirala and Jha (2003), Abera et al, (2004), Kumar and Singh (2004), Kaundal and Sharma (2006) Nadagoud et al, (2012), Shiri (2013), Nzuve et al, (2013), Kamutando et al, (2013). Anley et al, (2013), Tiwari et al, (2014) and Bisawas et al., (2014).…”
supporting
confidence: 62%
See 1 more Smart Citation
“…conditions were also reported by Agrwal et al., (2000), Dodiya and Joshi (2003), Nirala and Jha (2003), Abera et al, (2004), Kumar and Singh (2004), Kaundal and Sharma (2006) Nadagoud et al, (2012), Shiri (2013), Nzuve et al, (2013), Kamutando et al, (2013). Anley et al, (2013), Tiwari et al, (2014) and Bisawas et al., (2014).…”
supporting
confidence: 62%
“…The significant G x E interaction for various traits were also reported by Sharma and Saikia (2000), Dodiya and Joshi (2003), Singh et al, (2003), Abera et al, (2006), Admassu et al, (2008), Zaidi et al, (2008), Rahman et al, (2010), Arulselvi and Selvi (2010), Beyene et al, (2011), Shiri (2013, Nzuve et al, (2013), Kamutando et al, (2013) and Sserumaga et al, (2016).A perusal of stability parameters for grain yield per plant revealed that out of 67 genotypes 59 genotypes (18 parents, 37 hybrids and 4 checks) exhibited non-significant deviation from regression (S2di) and are as such predictable for this trait. Parental line L6 exhibited non-significant deviation from regression (S2di) and regression coefficient greater than unity (bi >1) with higher mean values than the population mean and would remain stable for grain yield per plant in favourable environments.…”
Section: Resultsmentioning
confidence: 59%
“…The similar observations were also noted earlier by Arulselvi and Selvi (2010) and Khaldun (2012). Nzuve et al (2013), Jha et al (2013), Abuali et al (2014) and Kumar et al (2014) also observed significant variance due to G, E and GxE interaction however the magnitude of SS due to environment was noted to be higher than the G and GxE.…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, by means of this method, it was apparently established that high and stable yields could be attained only in specific environment. Other researchers observed that GGE biplot analysis is a suitable device for detecting experimental environments to select best genotypes in field crops as well (Balestre et al, 2009;Ilker et al, 2009;Oliveira et al, 2010;Tonk et al, 2011;Khalil et al, 2011;Beyene et al, 2011, Nzuve et al, 2013Mortazavian et al, 2014;Miah et al, 2015).…”
Section: Relationship Among the Environmentsmentioning
confidence: 99%